2016
DOI: 10.1002/ejp.867
|View full text |Cite
|
Sign up to set email alerts
|

Short lasting transient effects of a capsaicin 8% patch on nociceptor activation in humans

Abstract: Axonal nociceptor function assessed by electrical excitability tests supplements threshold tests of nociceptive endings. The differential analgesic effects of 8% capsaicin patches may be attributed to the kinetics of capsaicin and the different depth of nociceptive nerve fibres, yet, the time course does not match the long-lasting analgesia observed in neuropathic pain patients treated with the same patch. WHAT DOES THIS STUDY ADD?: Axonal nociceptor function assessed by supra-threshold electrical excitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Unfortunately, we did not report the subjective pain intensity five minutes following the patch removal. A previous study showed that the pain NRS score during a 1-h capsaicin application had a peak of 6 ± 3 which declined to 5 ± 2 after 1 h of patch removal ( Landmann et al, 2016 ). Whether 5 min after patch removal could alter capsaicin concentration (and hence pain perception) remains unknown, but it cannot be excluded affecting EC recordings in the EO-EC group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not report the subjective pain intensity five minutes following the patch removal. A previous study showed that the pain NRS score during a 1-h capsaicin application had a peak of 6 ± 3 which declined to 5 ± 2 after 1 h of patch removal ( Landmann et al, 2016 ). Whether 5 min after patch removal could alter capsaicin concentration (and hence pain perception) remains unknown, but it cannot be excluded affecting EC recordings in the EO-EC group.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin activates the transient receptor potential vanilloid channel (TRPV1; Caterina et al, 1999). The prolonged activation of this channel, using continuous application of capsaicin, desensitizes and disrupts nociceptive nerve endings (Landmann et al, 2016). Although most studies emphasize the selective action of capsaicin on nerve endings related to unmyelinated C-fibre, several investigations showed that capsaicin also affects Adfibre free nerve endings, thus implying that also these nerve fibres express TRPV1 (Beydoun et al, 1996;Tympanidis et al, 2004;Mouraux et al, 2010).…”
Section: Capsaicin-induced Skin Denervationmentioning
confidence: 99%
“…Notably, HPT, which can be increased by capsaicin treatment, did not show signs of normalization during the repeated capsaicin treatments. This is unlikely to be related to the capsaicin treatments however, since previous studies have not shown any prolonged increase in HPT in healthy controls [19] or neuropathic pain patients following an 8% capsaicin treatment. Morever, WDT which is in fact profoundly increased by 8% capsaicin did normalize substantially in our patient [20] .…”
Section: Discussionmentioning
confidence: 73%